2010
DOI: 10.1111/j.1460-9568.2010.07102.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dopamine transporter DAT1 genotype on the neural correlates of cognitive flexibility

Abstract: Cognitive flexibility, the ability to adapt goal-oriented behaviour in response to changing environmental demands, varies widely amongst individuals, yet its underlying neural mechanisms are not fully understood. Neuropharmacological and human clinical studies have suggested a critical role for striatal dopaminergic function mediated by the dopamine transporter (DAT). The present study aimed at revealing the role of the DAT in the individual brain response stereotypy underlying cognitive flexibility. A task-sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 46 publications
5
39
2
1
Order By: Relevance
“…This crucial function involves the DA system (Cools, 2008;Garcia-Garcia et al, 2010a;Garcia-Garcia et al, 2010b;Kaplan and Oudeyer, 2007;DA Lewis et al, 2001;Mehta et al, 2000;Sawaguchi and Goldman-Rakic, 1994) putatively through a reciprocal relationship between PFC and striatal DA (Akil et al, 2003;Meyer-Lindenberg et al, 2002). This interplay is thought to regulate the stability and flexibility of mental representations, maybe through the modulation of the firing of prefrontal pyramidal neurons, which is enhanced during maintenance in the delay period of a memory task (Durstewitz et al, 2000) and is modulated by the DA neurotransmitter through stimulation of D1 receptors at the PFC (Durstewitz et al, 2000;Durstewitz and Seamans, 2002;Sawaguchi and Goldman-Rakic, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This crucial function involves the DA system (Cools, 2008;Garcia-Garcia et al, 2010a;Garcia-Garcia et al, 2010b;Kaplan and Oudeyer, 2007;DA Lewis et al, 2001;Mehta et al, 2000;Sawaguchi and Goldman-Rakic, 1994) putatively through a reciprocal relationship between PFC and striatal DA (Akil et al, 2003;Meyer-Lindenberg et al, 2002). This interplay is thought to regulate the stability and flexibility of mental representations, maybe through the modulation of the firing of prefrontal pyramidal neurons, which is enhanced during maintenance in the delay period of a memory task (Durstewitz et al, 2000) and is modulated by the DA neurotransmitter through stimulation of D1 receptors at the PFC (Durstewitz et al, 2000;Durstewitz and Seamans, 2002;Sawaguchi and Goldman-Rakic, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, if non-informatively cued switches influenced processing at a strictly sensory level, then target-locked brain activity should not be modulated by the interaction of the Cue type and Task condition factors. Several previous studies have shown that the mean amplitude of the cue-locked P3 component in the ERPs are modulated by both sensory updating and task switching, at least in the auditory modality [15], [19], [21]. Even though less well studied than the P3, the endogenous and fronto-centrally distributed P2 component has also been shown to be sensitive to change detection [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…FMRI research most consistently associates the 9R allele with increased reward reactivity in the striatum (Yacubian, Sommer et al 2007; Dreher, Kohn et al 2009; Forbes, Brown et al 2009). Although DAT is primarily expressed in striatum, evidence associates the 9-repeat allele with increased ventral striatal and dorsomedial PFC activation during working memory updating and task switching (Aarts, Roelofs et al 2010; Garcia-Garcia, Barcelo et al 2010), and increased PFC activation during inhibitory control, which was interpreted as supporting improved inhibitory control (Congdon, Lesch et al 2008; Congdon, Constable et al 2009). Developmental studies using the DAT1 polymorphism suggest that typically developing adolescents with the 9-repeat allele demonstrate reduced activation of prefrontal and striatal regions during inhibitory control (Braet, Johnson et al 2011), and reward prediction (Paloyelis, Mehta et al 2012).…”
Section: Da Inactivation Genes (Comt Dat1)mentioning
confidence: 99%